Utilization of learning media based on augmented reality on design material network topology - Rohandi, Manda; Pakaja, Jemmy A.; Mulyanto, Arip; Novian, Dian; A., Hermila; Ashari, Sri Ayu; Nugraha, Bariq (Indonesian Journal of Electrical Engineering and Computer Science, 2024)
Augmented reality (AR) is a growing technology that has great potential in the field of education. This article explores using AR as an interactive learning medium in a secondary education environment. The study involves the implementation of AR in network topology material to enhance student engagement and understanding. This research consists of the design and development of AR applications following the curriculum of the network topology subject at SMK Negeri 1 South Bulango using the waterfall model. The results showed that using AR-based learning media can increase student engagement in the learning process. Three-dimensional visualization of network topology design can improve students’ interest and motivation to understand the material better. AR allows students to interact directly with the network topology design model.